2019
DOI: 10.1007/978-3-030-33246-4_30
|View full text |Cite
|
Sign up to set email alerts
|

Business Object Centric Microservices Patterns

Abstract: A key impediment towards maturing microservice architecture conceptions is the uncertainty about what it means to design fine-grained functionality for microservices. Under a traditional service-oriented architecture (SOA), the unit of functionality for software components concerns individual business domain objects and encapsulated operations, enabling desirable architectural properties such as high cohesion and loose-coupling of its components. However, at present it is not clear how this SOA design strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Average of network. The average network bandwidth consumption for the entire system; Kb/s used by system or microservice ( De Alwis et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Average of network. The average network bandwidth consumption for the entire system; Kb/s used by system or microservice ( De Alwis et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such semantic relationships are highlighted by Pẽrez-Castillo et al's experiments [15], in which the transitive closure of strong BO dependencies derived from databases was used to recommend software function hierarchies, and by Lu et al's experiments [16], in which SAP ERP logs were used to demonstrate process discovery based on BOs. Also, our own previous research on microservice discovery based on BO relationship evaluation [17,18] showed the impact of considering semantic structural relationships in software remodularisation. However, to date, techniques related to semantic structural relationships have not been integrated with static syntactic techniques at the method level.…”
Section: Related Work and Techniques Used For Software Remodularisationmentioning
confidence: 94%
“…More recently, semantic knowledge available through BOs of enterprise systems has been exploited to improve the feasibility of applications' architectural analysis [16]. Our previous research on MS discovery from enterprise systems for cloud deployments, involving analysis of source code and systems logs, similarly exploits knowledge of BO relationships [17,18]. This was based on class-level feature set extractions for software remodularisation analysis: structural inheritance relationships (class supertypes and subtypes), structural interaction relationships (class level creations and invocations), structural class similarity (intra-class level), and class semantic properties (class and BO dependencies for BOs managed through classes).…”
Section: Introductionmentioning
confidence: 99%
“…Such semantic relationships are highlighted by the experiments conducted by Pẽrez-Castillo et al [12], in which the transitive closure of strong BO dependencies derived from databases was used to recommend software function hierarchies, and by the experiments conducted by Lu et al [13], in which SAP ERP logs were used to demonstrate process discovery based on BOs. Research conducted by De Alwis et al [14,15] on MS discovery based on BO relationship evaluation shows the impact of considering semantic structural relationships in software remodularization. However, to date, techniques related to semantic structural relationships have not been integrated with syntactic structural relationships and structural class similarity techniques.…”
Section: Related Work and Techniques Used For Software Remodularizationmentioning
confidence: 99%
“…In this matrix, again, rows correspond to classes, and columns correspond to unique words identified in step three of the algorithm that appear in the corresponding classes. The values in uwcount are then used in the sixth step to calculate the cosine similarity between the documents using COSINECAL function (see lines [12][13][14]. First, this function normalizes the term frequencies with the respective magnitude L2 norms.…”
Section: Clustering Discovery Algorithmsmentioning
confidence: 99%